Measuring the impact of tourism upon urban economies: A review of literature - Ugo Gasparino; Elena Bellini; Barbara Del Corpo; William Malizia (Fondazione Eni Enrico Mattei (FEEM), 2008)
Tourism is increasingly seen as a potential lever towards high economic growth, measured both in terms of income and employment. In recent years, interest in tourism has spread rapidly throughout many small and medium European cities, which previously have not considered themselves as tourist destinations. This paper reviews and summarises the existing literature on the economic assessment of tourism with the objectives of, firstly, identifying the main categories of impacts and, secondly, constructing an inventory of methodologies available to assess them. We will progress step by step, starting from the most simplistic approaches and relaxing assumptions as we proceed. Firstly, we assume a static setting, with spare capacity. In such a setting (partial equilibrium), prices do not respond to demand shocks: only quantities (production, income and jobs) adjust. Secondly, we relax this assumption and assume that there is no spare capacity: prices respond to increasing demand (general equilibrium), leading to reallocation of resources across sectors. We then move from a static to a dynamic setting and survey those contributions that look at the relationship between tourism specialisation and long-run growth.
Keywords: B41; C67; C68; L83; 330; Tourism; Economic Impacts; Input-Output Analysis; General and Partial Equilibrium Analaysis